Signifikansi Identifikasi Risiko sebagai Penopang Keberhasilan Program Kerja: Analisis Kritis, Kerangka Proses, dan Implikasi Strategisnya - Abd. Rohim; Nur Faizah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The successful implementation of an organizational work program depends heavily on management's ability to anticipate and manage the various forms of uncertainty that may arise. The risk identification process serves as the cornerstone of the entire risk management cycle, as it determines the effectiveness of subsequent preventive and remedial measures. This article critically examines the strategic importance of risk identification, outlines its systematic implementation stages, and evaluates its impact on achieving work program objectives. Employing a Systematic Literature Review (SLR) approach, this study gathers and synthesizes findings from credible academic sources published between 2020 and 2026. The results indicate that most work program failures stem not from a lack of resources, but from the organization's failure to identify potential obstacles at the planning stage. Structured risk identification has been shown to improve resource allocation accuracy, minimize potential cost and schedule overruns, and strengthen data-driven decision-making. The study recommends embedding a culture of risk awareness throughout every stage of work program management to ensure sustainability and the achievement of the organization's strategic goals.